A formação de leitores no 2º ano do ensino fundamental: um estudo na UEB Olavo Melo - SOUSA , Andréia Vaz Cunha de (2020)
This research refers to the study on the formation of readers in a class of 2nd year of Basic Education in Basic Education. The objective is to evaluate the theoretical and methodological concepts that support the reading practices in the Basic Education Unit Olavo Melo and its repercussion in the initial training of readers in the 2nd year of the class in question aiming at a proposal for intervention in these rites and trajectories, by identifying if the nature of the reading strategies involved in the initial training of readers, when analyzing the reading practices developed in the literacy classes and their contribution to literacy, and when making a proposal together with the teachers of the Unit in focus intervention, in view of the initial training of readers in the 2nd year of elementary school. It is problematic to understand to what extent the theoretical and methodological conceptions that support the reading practices in use have favored the initial training of readers of the evening shift in the rural environment of the municipal network of Paço do Lumiar in the last 24 months. The theoretical-methodological approach of cultural history is adopted based on the collection of historical data via bibliographic and documentary research, as well as the use of action research as a means of intervention aided by data collection instruments and techniques: observation, the questionnaire , the focus group and the interview. It is concluded that the negative aspects arising from a teaching of reading based on the encoding and decoding of letters, syllables and words can materialize in the school's formative process, since from the interventions we observed that the students understood that reading is a construction meaning, that they can establish relations with the text and that the opportunities to experience situations that involve writing and reading aiming at the social and practical use of citizenship are necessary as a suggested way to try to overcome the failure of the initial formation of students as readers.